2019
DOI: 10.17083/ijsg.v6i1.262
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary perspective on gamification: Mechanics, psychological mediators and outcomes

Abstract: As gamification literature has matured, the gap between how different domains apply the theory has widened. This has positioned gamification as being more dependent on context, rather than being an independent theory per se. To address this notion, three concepts are identified as being central for how a gamificator, the one responsible for gamifying, gamifies a process. These are mechanics, mental mediators and desired outcomes. Following this logic, a review was conducted using 77 (n) articles across seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 108 publications
1
19
0
1
Order By: Relevance
“…Gamification research has been criticized for yielding context-dependent results rather than a generalizable theory (Helmefalk, 2019). Unfortunately, gamification research has mostly focused on the effects of game mechanics on particular outcomes (eg, motivation and behaviour) while dismissing the psychological processes that mediate the relationship between these mechanics and outcomes (Sailer, Hense, Mayr, & Mandl, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gamification research has been criticized for yielding context-dependent results rather than a generalizable theory (Helmefalk, 2019). Unfortunately, gamification research has mostly focused on the effects of game mechanics on particular outcomes (eg, motivation and behaviour) while dismissing the psychological processes that mediate the relationship between these mechanics and outcomes (Sailer, Hense, Mayr, & Mandl, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When considering gamified technologies at face value, there is a tension between being easy to use via good user experience design, and being sufficiently challenging to be motivating via good game design ( Deterding, 2015 ). Furthermore, while immersion and similar flow-inducing techniques have been cited as advantages of gamification ( Baranowski et al, 2008 ; Helmefalk, 2019 ), the somewhat opposite approach of encouraging mindful, active self-reflection may also be conducive toward achieving mental health goals, for example, through learning and understanding complex situations ( Tyack and Wyeth, 2017 ). Similarly, Cheng et al (2018) found that participants perceived activities that required more active participation (e.g., creating, and physically typing, a message to a loved one) more helpful and meaningful than activities requiring less participation and effort.…”
Section: Developing and Evaluating Gamified Technologies For Mental Hmentioning
confidence: 99%
“…In their systematic review on gamified apps and technologies for mental health and wellbeing, Cheng et al (2019) provide a taxonomy of gamification elements that mental health technology developers may find a helpful frame of reference. Similarly, Helmefalk (2019) lists a number of psychological mediators synthesized from gamification articles across seven disciplines, and proposes that “gamificators,” or people who gamify, consider mechanics, psychological mediators, and desired outcomes (M-PM-O) when creating a gamified technology. Additionally, Ašeriškis and Damaševičius (2014) list a number of common “gamification patterns,” or design patterns commonly found in gamified systems, that can be used as reference when designing resource systems (such as for points) within gamified apps.…”
Section: Developing and Evaluating Gamified Technologies For Mental Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, gamification involves the identification, extraction, and application of individual game elements or limited, meaningful combinations of those elements [28]. A growing interest has been observed in applying gamification into diverse domains, such as health, education, human resource productivity, users' data collection, and customer participation, among others [12] [14] [20] [21]. It is believed that gamification can influence users to improve their motivation, to trigger behavioral changes, and to promote better collaboration [14].…”
Section: Introductionmentioning
confidence: 99%